Developing Tri Hita Karana-Based Balinese Klakat Tradition Augmented Reality Media to Enhance Creativity of Elementary School Students - Indrawan, I Putu Eka; Parmithi, Ni Nyoman; Anggreni, Ni Luh Putu Yesy (Jurnal Paedagogy, 2025)
This research aims to develop Augmented Reality (AR) media based on Tri Hita Karana to increasing the creativity of elementary school students and fostering a love for local culture. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the Analysis stage, studentsâ€™ needs in understanding spatial concepts through culturally based media were identified. The Design stage involved designing the AR Klakat Bali concept, including interactive content and cultural value integration. Next, the Development stage encompassed the creation and expert validation of the media by teachers and professionals using Aikenâ€™s V to ensure content validity. In the Implementation stage, the media was applied in learning at SD Negeri 6 Denpasar, with 46 first-grade students as research subjects. The final stage, Evaluation, assessed practicality and effectiveness using questionnaires and observations. Data analysis techniques included descriptive statistical analysis and qualitative data triangulation to ensure accuracy. The validation results showed that this media had a very high level of validity with an average Aiken’s V value of 0.995, indicating that the content, presentation, and characteristics of the application are very suitable for use in learning. In addition, the questionnaire results showed that students had a high interest in using AR Klakat Bali, with an average score of 3.137 on the aspects of interest, loyalty, care, and appreciation of local culture. The use of AR Klakat Bali not only helps students understand the concept of building space in mathematics learning, but also introduces them to the philosophy of Tri Hita Karana, which emphasizes the balance of human relationships with God, others, and the environment.